Analisis dan Perencanaan Sistem Drainase di Lingkungan Universitas Lampung (Studi Kasus Zona I : Fakultas Teknik, Fakultas Ekonomi dan Bisnis, Fakultas Ilmu Sosial dan Politik, Fakultas Hukum) - Jamaludin HN, .; Purwadi, Ofik Taufik; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain, 2018)
University of Lampung as one of the first and oldest public university in Lampung Province is one of the best universities in the region of Sumatra and continuously improve the quality of its academic, with the Accreditation A. Enhancement and infrastructure facilities university of Lampung continue, so can improving the academic quality or non-academic. The form of non-academic quality improvement is the environmental arrangement of one of its plans development of drainage system. This is intended to solve some of the flooding puddles that occurred at the time rainy season arrives because not optimal condition of existing drainage in University of Lampung region . The analysis conducted in this research includes hydrology analysis and hydraulics analysis using HEC-RAS 4.1.0 application. Hydrology analysis aims to calculate the design discharge using rational methods and modeling with HEC-RAS 4.1.0 application aims to determine the capacity of the water level existing channel. So it can be known where the position of the flood point and planning the new channel dimensions. Based on the analysis, the need for planning new drainage at some point indicating the occurrence of run off and inundation at Kantin Teknik Prasmanan. Planning of absorption wells and retention ponds is also very needed to overcome the problem of frequent flooding in Faculty of Engineering. It is also necessary to maintain channel maintenance in the form of channel normalization, garbage retaining lattice installation, and periodic cleaning of channels.Keywords: hydrology, hydraulics, HEC-RAS 4.1.0, drainage, absorption wells, andretention ponds.